KOMUNIKASI EFEKTIF DAN SISTEM INFORMASI GEOGRAFIS PADA TENAGA KESEHATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS KABUPATEN SEMARANG - Wulan, Widya Ratna; Pantiawati, Ika; Kusuma, Edi Jaya (Indonesian Journal of Health Information Management Services, 2025)
Effective communication training for Prolanis health workers is essential to improve the quality of interactions between health workers and patients. Good communication can influence patients' adherence to medication, understanding of their health condition, and following the chronic disease management program with discipline. In addition, Geographic Information System (GIS) training is becoming increasingly relevant in the context of Prolanis. By utilizing GIS, health workers can more effectively map the distribution of chronic diseases in Semarang Regency. This mapping aids in evidence-based decision-making, allowing health resources to be allocated more efficiently. GIS enables the identification of areas with high disease prevalence, so that interventions can be focused on areas that require more attention. It also supports preventive efforts to curb the increase in chronic disease cases. The implementation of Effective Communication and Geographic Information System (GIS) training for Prolanis health workers in Semarang Regency has several strategic objectives, both in the context of increasing the competence of health workers, strengthening the health service system, and contributing to the Merdeka Learning Campus Merdeka (MBKM) program, the Main Performance Indicators (KPI) of higher education, and the focus of community service.